Echocardiographic findings in left ventricular to right atrial communication - Saraçlar, Muhsin; Özkutlu, Süheyla; Bilgiç, Arman; İkizler, Coşkun (The Turkish Journal of Pediatrics, 1983)
Congenital LV-RA communication is a rare anomaly. The clinical diagnosis of this condition is extremely difficult. As a non-invasive method echocardiography appears to be useful in detecting this condition. In our four cases with this entity the characteristic M-Mode echocardiographic finding was systolic fluttering of the tricuspid valve. Vibrations of the tricuspid valve were anterior in three of our cases while in the fourth, where there was elevated RV pressure, they were posterior. Three of our four cases were operated on, and in the postoperative period abnormal echo findings had disappeared. In addition to echo findings of the tricuspid valve we recorded systolic fluttering of the interventricular septum in the outflow tract of the left ventricle in our fourth case.
Keywords: congenital cardiac anomaly; echocardiography; left ventricular to right atrial communication